Team work experiences in experimental toxicology research and in work setting survey promoted by E.C. Vigliani - Cirla, Angelo Maria (La Medicina del Lavoro, 2019)
In this work a personal experience within the Clinica del Lavoro “Luigi Devoto” of the University of Milan, in the period from 1965 to1975, is reported. The activity was focused on the teamwork in the field of the experimental research, to improve and stimulate new goals for young researchers, as proposed by the director E.C. Vigliani. It was mandatory that members with different education and skills would form a team, to freely pursue the same aim. Three experiences are described: the first was in the team of immunology and allergology, with the study of the delayed hypersensivity induced by berillium in guinea pig; afterwards, in the team of experimental toxicology, where the renal damage and the peripheral vascular resistances induced by exposure to cadmium, zinc, lead and mercury, were investigated; the last was in the team studying the asthmatic pathology induced by diisocyanates, where it was set, first in Italy, an original diagnostic occupational bronco provocative test. In these activities, a valuable support was given by the industrial hygiene laboratory and the biochemistry laboratory. The cultural changes after 1968 determined a decrease of experimental research. Instead, the Clinic was oriented to intervention in occupational settings, pursuing a scientific approach to assess the risk for health and to improve the hygienic conditions in the workplaces. Two typical examples are mentioned in which the work in team was useful to deal with these interventions, and a strong collaboration between occupational physicians and industrial hygienists was put in place. Finally the author left the Clinic to start the Lombardy experience of the territorial services of occupational health within the hospital of Lecco, in which an efficient laboratory of industrial hygiene laboratory was included. The team work methodology became active on the territory and handed down in the new culture of peripheral public services for occupational prevention as a good practice.